The Politics of Political Economists - Stigler, George (Quarterly Journal of Economics, 1959)
I. What is a conservative? 523. — II. The influence of the study of economics upon policy views, 524. — III. The cause of professional conservatism, 528. — IV. The scientific effects of conservatism, 530. — V. Concluding remarks, 532.